A Memristive Hyperchaotic System without Equilibrium - Viet-Thanh Pham; Christos Volos; Lucia Valentina Gambuzza (The Scientific World Journal)
A new memristive system is presented in this paper. The peculiarity of the model is that it does not display any equilibria and exhibits periodic, chaotic, and also hyperchaotic dynamics in a particular range of the parameters space. The behavior of the proposed system is investigated through numerical simulations, such as phase portraits, Lyapunov exponents, and Poincaré sections, and circuital implementation confirmed the hyperchaotic dynamic.